Lack of resolution sensor drives age-related cardiometabolic and cardiorenal defects and impedes inflammation-resolution in heart failure - Bochra Tourki; Vasundhara Kain; Amanda B. Pullen; Paul C. Norris; Nirav Patel; Pankaj Arora; Xavier Leroy; Charles N. Serhan; Ganesh V. Halade (2019)
Recently, we observed that the specialized proresolving mediator (SPM) entity resolvin D1 activates lipoxin A4/formyl peptide receptor 2 (ALX/FPR2), which facilitates cardiac healing and persistent inflammation is a hallmark of impaired cardiac repair in aging. Splenic leukocyte-directed SPMs are essential for the safe clearance of inflammation and cardiac repair after injury; however, the target of SPMs remains undefined in cardiac healing and repair. To define the mechanistic basis of ALX/FPR2 as a resolvin D1 target, ALX/FPR2-null mice were examined extensively. The systolic-diastolic heart function was assessed using echocardiography, leukocytes were phenotyped using flow cytometry, and SPMs were quantitated using mass spectrometry. The presence of cardiorenal syndrome was validated using histology and renal markers. Lack of ALX/FPR2 led to the development of spontaneous obesity and diastolic dysfunction with reduced survival with aging. After cardiac injury, ALX/FPR2-/- mice showed lower expression of lipoxygenases (-5, -12, -15) and a reduction in SPMs in the infarcted left ventricle and spleen, indicating nonresolving inflammation. Reduced SPM levels in the infarcted heart and spleen are suggestive of impaired cross-talk between the injured heart and splenic leukocytes, which are required for the resolution of inflammation. In contrast, cyclooxygenases (-1 and -2) were over amplified in the infarcted heart. Together, these results suggest interorgan signaling in which the spleen acts as both an SPM biosynthesizer and supplier in acute heart failure. ALX/FPR2 dysfunction magnified obesogenic cardiomyopathy and renal inflammation (↑NGAL, ↑TNF-α, ↑CCL2, ↑IL-1β) with elevated plasma creatinine levels in aging mice. At the cellular level, ALX/FPR2-/- mice showed impairment of macrophage phagocytic function ex-vivo with expansion of neutrophils after myocardial infarction. Lack of ALX/FPR2 induced obesity, reduced the life span, amplified leukocyte dysfunction, and facilitated profound interorgan nonresolving inflammation. Our study shows the integrative and indispensable role of ALX/FPR2 in lipid metabolism, cardiac inflammation-resolution processes, obesogenic aging, and renal homeostasis.